Design of genetic algorithm controller to fuel cell fed SEIG derived by DC motor - Talal Mahmood, Omar; S. Sultan, Nashwan; M. T. Ibraheem Alnaib, Ahmed (International Journal of Engineering and Technology, 2018)
This paper presents new method for driving Self-Excited Induction Generator (SEIG); DC motor is used for drive the SEIG as a prime-mover which feed from Fuel Cell (FC) via DC-DC buck converter. FC is considering one of the promising renewable energy. The SEIG loaded by external load. Two control loops has been designed to enhance the performance of the proposed system to normalizing speed of DC motor, both controller are designed using hybrid Proportional Integral (PI) based on Genetic Algorithm (GA); the first control loop used to control the output voltage of the buck converter by controlling the gating signals of the convertor to adjust the speed. The second controller regulates the hydrogen gas flow rate (i.e. fuel composition ratio of the fuel cell) with regard to the error signal of speed. The speed response of DC motor and the output power of the generator are investigated under many load conditions. Based on simulation results it is observed that the controllers provide robust adjusting for speed, beside the output voltage of the generator is pure sine wave beside its very little content of harmonics and thus the amplitude of Total Harmonic Distortion (THD) is 0.42% which considered is very low.